Systematic review to assess the possibility of return of cerebral and cardiac activity after normothermic regional perfusion for donors after circulatory death. Issue 3 (22nd January 2019) - Shapey, I. M.; Summers, A.; Augustine, T.; van Dellen, D.
Abstract : Background: Normothermic regional perfusion (NRP) is a novel technique that aids organ recovery from donors after circulatory death (DCDs). However, ethical concerns exist regarding the potential return of spontaneous cerebral and cardiac activity (ROSCCA). This study aimed to determine the likelihood of ROSCCA in NRP‐DCDs of abdominal organs. Methods: Extracorporeal cardiopulmonary resuscitation (ECPR) for refractory out‐of‐hospital cardiac arrest (OOHCA) was identified as a comparator for NRP‐DCDs and as a validation cohort. A systematic search identified all articles relating to NRP‐DCDs and ECPR‐OOHCA. Rates of ROSCCA and survival outcomes (ECPR‐OOHCA only) were recorded and analysed according to the duration of no perfusion. Results: In NRP‐DCDs, 12 of 410 articles identified by database searching were eligible for inclusion. There were no instances of ROSCCA recorded among 493 donors. In ECPR‐OOHCA, eight of 947 screened articles were eligible for inclusion (254 patients). Where the absence of perfusion exceeded 5 min in ECPR‐OOHCA, there were no survivors with a favourable neurological outcome. Conclusion: ROSCCA is unlikely following commencement of NRP and has not occurred to date. Strict observance of the 5‐min interval following asystole provides satisfactory assurance that ROSCCA will not occur following NRP. Abstract : Ethical concerns exist regarding the potential return of spontaneous cerebral and cardiac activity (ROSCCA) in normothermic regional perfusion (NRP)‐assisted donors after circulatory death (DCDs). This systematic review demonstrates that ROSCCA does not occur in a surrogate cohort of patients undergoing extracorporeal cardiopulmonary resuscitation for out‐of‐hospital cardiac arrest (ECPR‐OOHCA) where the no‐flow time exceeds 5 min. Strict observance of the 5‐min period following asystole provides satisfactory assurance that ROSCCA will not occur following NRP. Reassuring